White Sepulchres Palomares Disaster Semicentennial Publication - Howard, John (Biblioteca Javier Coy d'estudis Nord-Americans, 2016)
Published on the Palomares disaster?s 50th anniversary, this new documentary photobook questions the legacy of the worst nuclear weapons accident in history. With over 100 color images shot over five years in Almería, «White Sepulchres» records the aftermath of four U.S. nuclear bombs dropped in Palomares on 17 January 1966, making it the most radioactive town in Europe. Publicado en el año del 50 aniversario del desastre de Palomares, este nuevo fotolibro documental cuestiona el legado del peor accidente con armas nucleares de la historia. Con más de 100 imágenes a color tomadas a lo largo de cinco años en Almería, «White Sepulchres» registra las secuelas de cuatro bombas nucleares norteamericanas que cayeron el 17 de enero de 1966, y que hicieron de Palomares el pueblo más radioactivo de Europa.